Eye health in post-conflict and climate-vulnerable settings: Iraq as a case study for equitable, integrated primary eye care - Fatma Shakarchi (AJO International)
Purpose: Vision impairment affects one in four individuals globally, disproportionately affecting low- and middle-income countries, particularly in conflict- and climate-affected settings. This brief communication uses Iraq as a case study to examine how these intersecting challenges impact eye health systems. We also aim to identify strategies for strengthening equitable, integrated primary eye health. Design: A narrative case study. Methods: We analyzed national health data, health system reports, and international comparator models to assess how eye care services are distributed, accessed, and integrated within Iraq’s primary healthcare system. Special attention was given to socioeconomic disparities, post-conflict infrastructure, and climate vulnerability. Findings: Only 2 % of Iraq’s primary health centers offer eye-related services, which contributes to overburdened tertiary hospitals, and more than half of hospital consultations are for conditions manageable at the primary level.11 Iraqi Ministry of Health. Annual Statistical Report 2020 [Internet]. Available from: https://moh.gov.iq/upload/1540.pdf Access is further limited by financial barriers, uneven geographic distribution of specialists, and lack of insurance coverage. Eye health integration into primary healthcare is hindered by systemic and resource limitations. Conclusions: Iraq’s experience highlights the urgent need for equitable, community-based eye care systems in fragile settings. Addressing these gaps is essential for advancing universal health coverage and meeting global development goals.